1988
DOI: 10.1159/000146482
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Lumbar Vertebral Canal

Abstract: In a series of 215 anteroposterior X-ray films, a study was made of the horizontal distance between the pedicles of each lumbar vertebra, first of all sequentially, describing the morphology adopted by the lateral limits of the canal, and secondly determining the absolute value for each level separately and in relation to the variables of sex and age. The absolute value of this distance at each level is related to the thickness of the pedicles and the width of the vertebral bodies of L3 and L4. The values obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
1
12
1
2
Order By: Relevance
“…The interpedicular distance of the patients in our study was greater than that of Nigerians, Saudis and Koreans, but less than that of Spanish, Indian and healthy Turkish participants. 13,[16][17][18][19] The transverse diameter of the vertebral body in our population was similar to that observed in Nigerians, but was less than that seen in healthy Turkish people. 16,19 The cephalocaudal diameter of the pedicle is greatest at T12 and L1.…”
Section: Discussionsupporting
confidence: 74%
“…The interpedicular distance of the patients in our study was greater than that of Nigerians, Saudis and Koreans, but less than that of Spanish, Indian and healthy Turkish participants. 13,[16][17][18][19] The transverse diameter of the vertebral body in our population was similar to that observed in Nigerians, but was less than that seen in healthy Turkish people. 16,19 The cephalocaudal diameter of the pedicle is greatest at T12 and L1.…”
Section: Discussionsupporting
confidence: 74%
“…The changes of canal dimensions according to age in the present study were different from the Spanish 16 and Korean 15 series. In age group over 60 years, the midsagittal diameter was smaller than those of younger age group as a result of the hypertrophy or degenerative process of the spine.…”
Section: Discussioncontrasting
confidence: 85%
“…Other studies have been reported by Amonoo-Kuofi [9] on Nigerians, Postacchini et al [10] on Italians and Indians, Picraetal. [11] on Spanish subjects and Amonoo-Kuofi et al [12] on Saudis. Most importantly, the comparative studies by AmonooKuofi [9], Postacchini et al [ 10] and Piera et al [11] indi cated that there are morphometric differences between races.…”
Section: Introductionmentioning
confidence: 93%
“…[11] on Spanish subjects and Amonoo-Kuofi et al [12] on Saudis. Most importantly, the comparative studies by AmonooKuofi [9], Postacchini et al [ 10] and Piera et al [11] indi cated that there are morphometric differences between races. In addition, Leiviska et al [13] reported in 1985 that the size of the spinal canal is related to body stature.…”
Section: Introductionmentioning
confidence: 93%